Global Development and Environment - Joe Williams; James Duminy (Bristol University Press, 2025)
Available open access digitally under CC-BY licence. Development and environmental challenges are often framed at the global or planetary scale, but in a vague or apolitical manner. This book develops a theoretically rigorous and politicized concept of the planetary to intervene in contemporary debates on global development and to enhance our critical understanding of development as we approach the second quarter of the twenty-first century. Chapters explore key themes and processes including urbanization, demographic change, health, financialization, and infrastructure development. Referencing diverse cases and examples drawn from across the world, the book argues that the futures of global development are inseparable from environmental challenges and transformations.